Ustekinumab for the treatment of moderate to severe ulcerative colitis: a multicentre UK cohort study. Issue 6 (28th April 2022) - Honap, Sailish; Al-Hillawi, Lulia; Baillie, Samantha; Bancil, Aaron; Matini, Lawrence; Lau, Rebecca; Kok, Klaartje Bel; Patel, Kamal; Walsh, Alissa; Irving, Peter M; Samaan, Mark A
Abstract : Objective: Ustekinumab is an interleukin-12/interleukin-23 receptor antagonist licensed for the treatment of ulcerative colitis (UC). Clinical trial data were promising; however, real-world data are limited. We assessed the safety and effectiveness of ustekinumab in UC in a real-world setting. Design/method: This was a multicentre, retrospective, observational cohort study between February 2020 and January 2022. Disease activity was assessed using the Simple Clinical Colitis Activity Index (SCCAI). Clinical remission was defined as a SCCAI≤2. The primary endpoints were rates of corticosteroid-free remission (CSFR) at week 16 and at week 26. Objective outcomes, including faecal calprotectin (FCAL), were also collected. Results: 110 patients with UC (65% male; median age 40 (IQR range 29–59); 96% with prior biologic and/or tofacitinib exposure) had a median follow-up of 28 weeks (IQR 17–47). CSFR was 36% (18/50) at week 16% and 33% (13/39) at week 26, corresponding with a significant fall in SCCAI from 6 (IQR 4–8) at baseline to 3 (IQR 0–5) at week 26, p<0.001. By week 16, there was improvement of median FCAL measurements, which fell from a baseline of 610 µg/g (IQR 333–1100) to 102 µg/g (IQR 54–674) at week 16. At the end of follow-up, 15% (17/110) had discontinued treatment; 13 patients due to primary non-response or loss of response, and 1 patient for family planning. Treatment was discontinued in three patients due to adverse events. Conclusion: In the largest real-world study to date, ustekinumab was effective with a reassuring safety profile in a refractory cohort of patients.